Teacher Experiences In Performance Management System (Pms) In Zimbabwe: Focus On Assessment Reviews And Teachers’ Response - Dzimiri, Wonderful; Mkosana, Canaan (Advances in Social Sciences Research Journal, 2017)
This study investigated teacher experiences of, and response to the manner they were assessed or appraised in implementation of Performance Management System (PMS) in Zimbabwe amid concerns over difficulties in the determination of the link between an individual’s job performance and organizational performance, subjectivity in the conduct of performance appraisals and the interplay of personal biases in performance assessment and ratings. Using mixed methods approach, research designs included the survey, case study and phenomenology. From two randomly selected districts of the Midlands Province, 5.2% of primary school teachers and 3.5% of secondary school teachers were randomly sampled from randomly picked schools in the two districts. School heads of sampled schools and district education officers were purposively selected. Data generation tools included questionnaire, semi-structured interviews, document analysis and non-participant observation. Analysis employed descriptive statistics (numbers and corresponding percentages) for quantitative data, and thematic analysis for qualitative data respectively. The major finding was that training on PMS was inadequate for supervisors and teachers. Consequently, teachers and supervisors did not understand what they were expected to do in PMS. Furthermore, school heads’ concern lay with summative supervision and enforcement of PMS through coercive, dictatorial approaches akin to policing for compliance. Without adhering to procedure, crisis management combined reviews and appraisal ratings in a single meeting in some cases. Teachers perceived supervisors’ role negatively, resulting in teachers cheating or resisting, thus defeating professional development benefits of PMS. Findings point to the need for training and resourcing, or modification of the system to suit context.